ASET MANAJEMEN RUMAH SAKIT BERBASIS WEB SYSTEM - Angelina Permatasari (Conference In Business, Accounting, And Management (CBAM), 2015)
The latest development, asset management increased its scope to be able to monitor the performance of operational assets and investment strategies for asset optimization. When the development of the set trying to be explored in the context of asset management by local governments in Indonesia, is not yet fully understood by the asset management area. The method used is Evidence base and quality management policy. Making evidence-based quality management policies, namely in asset management web-based hospital system will provide a valuable opportunity to manage assets hospital with a quality policy making because based on evidence. Asset Management application design Hospitals web base system as a tool that is helpful in the management of Asset Management in the Hospital so that these activities can be run with the economic, effective and efficient. Â Keywords: asset management, hospital, evidence based, web system